2015
DOI: 10.1149/2.0571510jes
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Model of Four-Line Probe to Determine Conductive Properties of Thin-Film Battery Electrodes

Abstract: Measurement of the electronic conductivity of porous thin-film battery electrodes poses significant challenges, particularly when the film is attached to a metallic current collector. We have developed a micro-four-line probe and testing procedure that overcomes many of these difficulties while relying on principles similar to commonly used four-point probes. This work describes a mathematical model that enables rapid inversion of the data collected by such experiments to compute two properties: bulk electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…It was found that, as a general rule, the distance between the two outer lines of the probe should be approximately the same as the sample film thickness. 1 With the above considerations in mind, the lines were designed to be 10 μm wide and 3 mm long, with 10 μm spacing between them, as shown in Fig. 1.…”
Section: Probe and Fixture Designmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that, as a general rule, the distance between the two outer lines of the probe should be approximately the same as the sample film thickness. 1 With the above considerations in mind, the lines were designed to be 10 μm wide and 3 mm long, with 10 μm spacing between them, as shown in Fig. 1.…”
Section: Probe and Fixture Designmentioning
confidence: 99%
“…13 The probe template was designed to yield 10 μm wide lines, but because of nearly isotropic electroplating on the sides as well as the tops of the lines, at the completion of the process the lines had widened to 12 μm. Practical adaptation of mathematical model.-As specified by the mathematical model, 1 two different electrical configurations must be used with the μ4LP to estimate the bulk conductivity and interfacial resistance. The configurations are referred to as the tangential and orthogonal experiments.…”
Section: Probe and Fixture Designmentioning
confidence: 99%
“…The peak at 1620 cm −1 for alginate/PEDOT:PSS is attributed to the expansion of vibrations of -C=N groups, which are produced through the chemical reaction of -OH in oxidized starch and H 2 N - in starch from wheat. In addition, the peak at 1326 cm −1 is attributed to alginate with bending oscillations -CH,–SO 3 or -N-CO-CH 2 - groups, which are from alginate/PEDOT:PSS [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The electrical resistance (R) of each gel was measured during drying using a four-line probe method. The resistance of the plate was determined using the following equation [ 42 ]: where w is the width of the sample (2.5 cm) and d is the spacer between the leads (0.35 cm).…”
Section: Methodsmentioning
confidence: 99%
“…The electrical conductivity measurements of both ACWH and ACWH/S samples were carried out using the four-line probe method at room temperature. A current variation of 0.01-0.05 mA from a DC source is applied to the two outer probes, and then the resulting voltage is measured at the two inner probes with a digital multimeter [25,26]. Based on the current and voltage curves, the resistivity and conductivity values can be determined.…”
Section: Conductivity Measurementmentioning
confidence: 99%